2021
DOI: 10.1085/jgp.202112899
|View full text |Cite
|
Sign up to set email alerts
|

The M1 and pre-M1 segments contribute differently to ion selectivity in ASICs and ENaCs

Abstract: The ability to discriminate between different ionic species, termed ion selectivity, is a key feature of ion channels and forms the basis for their physiological function. Members of the degenerin/epithelial sodium channel (DEG/ENaC) superfamily of trimeric ion channels are typically sodium selective, but to a surprisingly variable degree. While acid-sensing ion channels (ASICs) are weakly sodium selective (sodium:potassium ratio ∼10:1), ENaCs show a remarkably high preference for sodium over potassium (&g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, we found that larger nitrogen-based cations, ammonium and methylammonium, were much less permeant than Na + in FaNaC1 (Fig. 4f), as observed for ENaC 33 but different from ASIC1, which conducts substantial ammonium and methtylammonium current 34,35 . This suggests that FaNaC1 adopts a narrower open-channel pore than ASIC1, as represented by our FMRFa-gated, diminazene-blocked structure, and that FaNaC1 presumably passes partly dehydrated Na + ions.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, we found that larger nitrogen-based cations, ammonium and methylammonium, were much less permeant than Na + in FaNaC1 (Fig. 4f), as observed for ENaC 33 but different from ASIC1, which conducts substantial ammonium and methtylammonium current 34,35 . This suggests that FaNaC1 adopts a narrower open-channel pore than ASIC1, as represented by our FMRFa-gated, diminazene-blocked structure, and that FaNaC1 presumably passes partly dehydrated Na + ions.…”
mentioning
confidence: 52%
“…Nonetheless, a better resolved picture of ion conduction throughout the superfamily emerges from the comparison of FaNaC1 and distantly related ASIC1 pores. FaNaC1 is more closely related to ENaC 8,47,48 , both of these channels are poorly permeable to nitrogen-based cations larger than Na + 33 , and our FaNaC1/FMRFa/diminazene structure reveals an ion pathway slightly narrower than both ASIC1 and voltage-gated sodium channels 11,49 , both of which pass ammonium, methylammonium, and hydroxylamine relatively well 34,35,50 . Taken together, our capture of FaNaC1 in different functional states describes the mechanism by which FMRFa elicits excitatory neuronal signals and offers a template for future studies dissecting channel gating and ion conduction in DEG/ENaCs.…”
Section: Discussionmentioning
confidence: 80%
“…2 The role of pre-TM1 and TM1 residues in ion selectivity have recently been shown, supporting the structural observations. 13…”
mentioning
confidence: 99%